Genealogia histórica do campo jurídico brasileiro: liberalismo-conservador, autoritarismo e reprodução aristocrática - Felipe Araujo Castro (2018)
We begin from the hypothesis that the laws interpretation are made by concrete juridical agents that have strong empathy with the political, economic and cultural elites; forged while sharing spaces of socialization that built similar worldviews. That scenario has a significant impact on judicial practice, which tends to benefit these elite groups, where the magistrates were always included. In this sense, the main objective of our thesis is to uncover the association between (i) an aristocratic social reproduction profile, (ii) authoritarian practices and (iii) the hegemonic presence of a liberal-conservative thought existing in the praxis of the legal field but hidden in its theory. The legitimating discourses over contemporary Western Law in the context of liberal democracies are based on the idea that constitutionalism is not only capable, but represents the best strategy perhaps the sole path for the promotion and assurance of modern ideals of freedom and equality; while the history of the Brazilian legal field is marked by a strong deference to the unequal established powers; therefore contradicting its discourse of legitimation. In the task of correctly understanding the social relations established in the spaces of formation and praxis of juridical agents in Brazil, the most appropriate option appears as the repertoire of reflexive sociology of the French author Pierre Bourdieu, presented in the first chapter. We have used this theoretical framework to demonstrate, in the second chapter, how the main characteristics present in the national legal field (conservative liberal thinking, authoritarian practices and aristocratic reproduction) are, in fact, genetic elements from these spaces, that is, they have been constituted since the emergence of the legal field as a relatively autonomous social sphere - discussion made in the third chapter. Chapter Four closes our critical review about the historical genealogy of the national legal field by focusing on the role played by juridical agents during the most recent transition period held between the military regime (1964-85) and our present democracy, relating this dynamics to the contribution of the Brazilian legal field in the ongoing political crisis. The undertaking of a historical genealogy, in the terms proposed, aims to reveal the strong contradictions between the main genetic characteristics of the national legal field and the contemporary legitimation discourse of their competences. Following the Bourdieusian intuition that institutions are transformed to perpetuate the sense of their game, representing the general behavior of their practices developed in time, we try to demonstrate how the conservative origin of the national juridical field and the absence of significant ruptures with the main characteristics of these spaces were decisive aspects for the configuration of the current functioning of the field, marked more by the imposition of obstacles to social justice than its implementation.